How Much Tumor Volume Is Responsible for Development of Clinical Symptoms in Patients With Convexity, Parasagittal, and Falx Meningiomas? - Shuhei Yamada (Frontiers Media S.A., 2021)
Purpose: Meningiomas are the most common primary intracranial neoplasms and clinical symptom appearance depends on their volume and location. This study aimed to identify factors that influence clinical symptoms and to determine a specific threshold tumor volume for the prediction of symptomatic progression in patients with convexity, parasagittal, and falx meningiomas.Materials and Methods: We retrospectively studied patients with radiologically suspected convexity, parasagittal, or falx meningiomas at our institution.Results: The data of three hundred thirty-three patients were analyzed. We further divided patients into two groups based on clinical symptoms: an asymptomatic group (250 cases) and a symptomatic group (83 cases). Univariate analysis revealed significant differences between the groups in terms of sex (p = 0.002), age at the time of volumetric analysis (p < 0.001), hyperintense lesions on T2-weighted images (p = 0.029), peritumoral edema (p < 0.001), maximum tumor diameter (p < 0.001), and tumor volume (p < 0.001). Further multivariate analysis revealed significant differences between the groups in terms of age at the time of volumetric analysis (p = 0.002), peritumoral edema (p < 0.001), and tumor volume (p < 0.001). The receiver operating characteristic curve revealed a threshold tumor volume of 21.1 ml for predicting whether a patient would develop symptoms (sensitivity 0.843, specificity 0.880, an area under the curve 0.919 [95% confidence interval: 0.887–0.951]).Conclusion: We identified factors predictive of clinical symptoms in patients with convexity, parasagittal, and falx meningiomas and determined the first-ever threshold tumor volume for predicting symptomatic progression in such patients.